2006
DOI: 10.1007/s11104-006-9001-y
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi enhance root cadmium and copper accumulation in the roots of the salt marsh plant Aster tripolium L.

Abstract: It is known that vegetation plays an important role in the retention of heavy metals in salt marshes by taking up and accumulating the metals. In this study, we investigated whether arbuscular mycorrhizal fungi (AMF) increase Cd and Cu uptake and accumulation in the root system of the salt marsh species Aster tripolium L., and whether indigenous AMF isolated from polluted salt marshes have higher capacity to resist and alleviate metal stress in A. tripolium than isolates of the same species originated from non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 33 publications
(39 reference statements)
0
22
0
1
Order By: Relevance
“…Gonzalez-Chavez et al (2002) have demonstrated that various Glomus species can store Cu in their mucilaginous outer hyphal layer and in the cell wall. An increase of Cu concentrations in plants roots was previously reported in Aster tripolium L. inoculated with G. geosporum, however this increase was not associated with a change in translocation to shoots (Carvalho et al 2006). Restriction of Cd transfer into shoots caused by G. mosseae has been observed in clover species (Joner and Leyval 1997;Vivas et al 2003).…”
Section: Discussionmentioning
confidence: 71%
“…Gonzalez-Chavez et al (2002) have demonstrated that various Glomus species can store Cu in their mucilaginous outer hyphal layer and in the cell wall. An increase of Cu concentrations in plants roots was previously reported in Aster tripolium L. inoculated with G. geosporum, however this increase was not associated with a change in translocation to shoots (Carvalho et al 2006). Restriction of Cd transfer into shoots caused by G. mosseae has been observed in clover species (Joner and Leyval 1997;Vivas et al 2003).…”
Section: Discussionmentioning
confidence: 71%
“…Estuarine salt marshes are often located close to urbanized and industrialized areas receiving discharges of pollutants such as heavy metals (Carvalho et al 2006). Although salt marshes are among the most productive systems of the world, these areas are also recognized as important sinks for metals (Vinagre Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These authors, however, did not consider the putative impact of salinity on Cu absorption and accumulation by the plant. Nevertheless, salt marshes are effective sinks of Cu originating from anthropogenic activities (Carvalho et al 2006;Reboreda and Caçador 2007). Although the influence of salinity on Cu absorption has been exhaustively considered in marine invertebrates (Grosell et al 2007;Lee et al 2010), algae (Ratkevicius et al 2003) and cyanobacteria (Surosz and Palinska 2000), data concerning higher plants are crucially missing.…”
mentioning
confidence: 99%
“…Using radiotracer flux analyses, the significant accumulation of Cd found in the vacuolar compartment has been suggested as an essential Cd detoxification mechanism in the ectomycorrhizal fungus Paxillus involutus (Blaudez et al, 2000b). Indeed, a number of recent data support the hypothesis that mycorrhizal fungi play a filtering/sequestering role on plant roots (Arriagada et al, 2010;Bissonnette et al, 2009;Carvalho et al, 2006;Christie et al, 2004;Cobbett and Goldsbrough, 2002;Colpaert et al, 2004;Lee et al, 2003;Mathur et al, 2007), enhancing root to shoot metal ratio and increasing survival rate in harsh conditions (Leung et al, 2007).…”
Section: Introductionmentioning
confidence: 99%